2022
DOI: 10.1111/geb.13563
|View full text |Cite
|
Sign up to set email alerts
|

Compound impact of land use and extreme climate on the 2020 fire record of the Brazilian Pantanal

Abstract: Aim: Our aim was to quantify the influence of climate and land use on major fires that occurred during the 2020 drought over the Brazilian Pantanal region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 72 publications
3
13
0
Order By: Relevance
“…The authors further found that there was large spatial variability in post‐fire changes in carbon stocks, related to pre‐fire biomass, but also other interacting processes, most likely pre‐fire drought stress and post‐fire biotic interactions (insect defoliation). Similarly, Ferreira Barbosa et al (2022) observed large spatial variation in estimated carbon emissions from the Brazilian Pantanal fires, linked to land use, with forests estimated to produce much greater pyrogenic carbon emissions than natural or anthropogenic pastures and grasslands. Importantly, Nolan et al (2022) also found that the consequences of fire on carbon fluxes are likely to extend well beyond the initial pyrogenic carbon emissions, with some forest types exhibiting over twice the amount of dead biomass in burned compared to unburnt forest.…”
Section: How Did the 2020 Fires Impact Species Vegetation Communities...mentioning
confidence: 95%
See 4 more Smart Citations
“…The authors further found that there was large spatial variability in post‐fire changes in carbon stocks, related to pre‐fire biomass, but also other interacting processes, most likely pre‐fire drought stress and post‐fire biotic interactions (insect defoliation). Similarly, Ferreira Barbosa et al (2022) observed large spatial variation in estimated carbon emissions from the Brazilian Pantanal fires, linked to land use, with forests estimated to produce much greater pyrogenic carbon emissions than natural or anthropogenic pastures and grasslands. Importantly, Nolan et al (2022) also found that the consequences of fire on carbon fluxes are likely to extend well beyond the initial pyrogenic carbon emissions, with some forest types exhibiting over twice the amount of dead biomass in burned compared to unburnt forest.…”
Section: How Did the 2020 Fires Impact Species Vegetation Communities...mentioning
confidence: 95%
“…The Australian wildfires burned a range of forest types including drier forests where fires typically recur every 10–20 years, to rain forests that persist in fire refugia (Bowman, 2000; Le Breton et al, 2022). In the Pantanal, the fires burned both forested areas that have not burned for over 18 years, as well as grasslands that regularly burn (Ferreira Barbosa et al, 2022). Despite these differences, the 2020 megafires have raised common questions, including (a) how do we define ‘megafires’?…”
Section: : a Year Of Megafiresmentioning
confidence: 99%
See 3 more Smart Citations